Early Readmissions After Hospitalization for Posterior Reversible Encephalopathy Syndrome. (1st November 2022) - Garg, Aayushi; Elmashala, Amjad; Roeder, Hannah
Abstract : Background and Objectives: To evaluate the frequency, etiologies, and risk factors for 90-day readmissions after hospitalization for posterior reversible encephalopathy syndrome (PRES). Methods: Data were obtained from the Nationwide Readmissions Database 2016–2018. Patients with a primary diagnosis of PRES, survival to discharge, and known discharge disposition were included. The primary outcome was nonelective readmission within 90 days of discharge. Survival analysis was performed, and independent predictors of readmission were analyzed using multivariable Cox proportional hazards regression. Results: Based on the study inclusion criteria, 6, 155 eligible patients were included (mean ± SD age: 55.9 ± 17.3 years, female: 71.0%). Nonelective readmission within 90 days of discharge occurred for 1, 922 (31.2%) patients. Of these, 617 readmissions were due to PRES-related or neurologic etiologies and the remaining 1, 305 readmissions were due to non-neurologic conditions. In multivariable analysis, age was inversely associated with the risk of readmission (hazards ratio [HR] 0.92 for every 10 years increase in age, 95% CI 0.88–0.97). Patients with diabetes (HR 1.21, 95% CI 1.04–1.42), systemic lupus erythematosus (HR 1.42, 95% CI 1.03–1.96), acute kidney injury (HR 1.28, 95% CI 1.11–1.47), and a higher Charlson comorbidity index score (HR 1.09, 95% CI 1.06–1.13) were more likely to be readmitted. Furthermore, patients admitted at large bed size hospitals (HR 1.19, 95% CI 1.03–1.39), those with a longer length of stay (HR 1.01, 95% CI: 1.00–1.02), and those not discharged to home (HR 1.33, 95% CI: 1.14–1.55) during the index hospitalization were also at a higher risk for readmission. Discussion: Nearly one-third of patients hospitalized because of PRES are readmitted within 90 days of discharge, and approximately one-third of these readmissions are due to PRES-related or neurologic etiologies. Younger age, a higher comorbidity burden, a longer length of hospital stay, and discharge disposition other than to home are independently associated with the risk of readmission.